(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
In June 2013, a pluriannual project has been started aimed to study the entire complex of the Imperial Villa of Tiberius at Sperlonga (LT), under the direction of Prof. Fabrizio Slavazzi (Università degli Studi di Milano) and in accordance with the Superintendence for Archaeological Heritage of Lazio. Initial investigations conducted by the team of the University of Milan, made it possible to draw up a sustained preliminary program of action that will lead in the future to investigate all the structures currently in light and promote the excavation of the areas still unexplored and the study of materials found in old and new digs.